Influence of the vegan diet on sports performance: Review article - Saraiva de Sousa, P. F. (Sustainability and Sport Science Journal, 2024)
Being healthy is a prerequisite for becoming a successful athlete. Most scientific evidence strongly associates a well-planned Vegan diet with health, successful body weight control, a preventive measure and, in some cases, the end and reversal of some of the most common noncommunicable chronic diseases. However, despite the solid health benefits of these diets, Vegan athletes are often confronted with prejudices for unfounded doubts and motives. Through the analysis of existing literature, the objectives of the present study were to explore the various advantages and risks of the Vegan diet for the health of sportsmen and women, whether in the context of competition or not and analysethe influence of this type of diet on the sports performance of athletes, when compared to omnivorous athletes. As can be seen, the literature on this topic is quite scarce and, apparently, performance is not boosted depending on the type of diet adopted.With this knowledge intended to demonstrate that vegan diets are compatible with sports performance, thus being able to encourage athletes and their families, coaches and health and sports experts to have a more open mind when an athlete expresses their desire to adopt a Vegan diet.